Modulatory effects of White Tea (Camellia sinensis L.) on genotoxicity in Streptozotocin and Cyclophosphamide-treated Drosophila melanogaster’: Modulatory effects of White Tea on genotoxicity - FİDAN, Mehmet; AYAR, Arif (Progress in Nutrition, 2021)
In the present study, it was aimed to determine the antigenotoxic activity of white tea against the genotoxic effect caused by two different alkylating antineoplastic cancer drugs streptozotocin (STZ) and cyclophosphamide (CP) in Drosophila melanogaster through the somatic mutation and recombination test (SMART). During the application of SMART, two different mutant strains were used in the genome of D. melanogaster, with the determinant genes being recessive flare (flr3) and multiple wing hairs (mwh), respectively. Trans-heterozygous larvae of 72±hours, obtained through the crossbreeding of these two mutant strains, were chronically fed with white tea extract of different concentrations (0.625, 1.25, 2.50, and 5 mg/mL). In our study, the LD50 values of the relevant drugs were also found (STZ: 0.25 mg/mL, CP: 2.5 mg/mL), and it was determined that both drugs have a fairly high genotoxic effect (p